Murder at an Irish bakery - O'Connor, Carlene (O'Connor, Carlene. Irish village mystery, 2023)
"In Kilbane, opinions are plentiful and rarely in alignment. But there's one thing everyone does agree on--the bakery in the old flour mill, just outside town, is the best in County Cork, well worth the short drive and the long lines. No wonder they're about to be featured on a reality baking show. All six contestants in the show are coming to Kilbane to participate, and the town is simmering with excitement... As for the competitors themselves, not all are as sweet as their confections. There are shenanigans on the first day of filming that put everyone on edge, but that's nothing compared to day two, when the first round ends and the top contestant is found face-down in her signature pie"--